Contrast-enhanced ultrasound of pancreatic melanoma: A case report and literature review - Yuan, Zhiqiang; Yan, Hualin; Ling, Wenwu; Luo, Yan (Frontiers in Oncology, 2022)
Melanoma is a malignant tumor that originates from melanocytes, most of which are of cutaneous origin. Most melanomas identified in the pancreas are metastatic, and primary pancreatic melanoma is extremely rare and has rarely been discussed. The correct preoperative diagnosis of pancreatic metastatic melanoma, especially primary melanoma, is challenging. Herein, we report a 43-year-old man who presented to our hospital due to unexplained left abdominal distension and pain. Abdominal ultrasound examination demonstrated multiple space-occupying lesions of the pancreas, and hypoechoic masses partially filled the splenic vein behind the pancreatic body. In the contrast-enhanced ultrasound (CEUS), all of these lesions showed iso-enhancement to slight hypo-enhancement in the arterial phase and hypo-enhancement in the venous phase. Masses in the splenic vein also showed hypo-enhancement. Imaging features suggested that the pancreatic lesions were malignant tumors. The tumor markers carcinoembryonic antigen, carbohydrate antigen 125 and carbohydrate antigen 19-9 were within normal limits. Based on clinical symptoms, imaging findings and incidence of pancreatic tumors, the patient's clinical diagnosis was pancreatic carcinoma. Surgery was performed for the patient, while postoperative pathology confirmed malignant melanoma of the pancreas. Therefore, it is significant to identify the clinical and imaging manifestations of pancreatic melanoma in order to better manage the disease. Herein, we reported this case and reviewed the literature from 2000 to 2021 on the clinical and imaging features of 26 patients with pancreatic melanoma. It may improve clinicians’ awareness of the clinical and imaging performance of pancreatic melanoma, resulting in improved diagnosis, differential diagnosis, treatment, and outcomes.